Rationality, Obstruction and Identity Deconstruction —Focusing on Sir. Peter Shaffer's Trilogy of Faith - Jiao, Qianqian (The journal of contemporary issues in business and government, 2021)
Peter Shaffer is an outstanding British playwright in the 20th century. His plays "The Royal Hunt of the Sun", "Equus" and "Amadeus" are called "Faith Trilogy". The eternal conflict between rationalism and irrationalism prompted Schaeffer to re- flect on the enslavement of human nature by reason under the rule of instrumental reason. He tried to rebel against rational hegemo- ny through belief, and proposed that only by seeking faith and spiritual God can human beings escape the shackles of rational- ism. This paper first explores the philosophical source of Schaf- er's anti rational thought, that is, the confrontation and conflict between rationalism and irrationalism. Secondly, it studies the social source of Schafer's anti rational thought, taking the critical theory of instrumental rationalism as an example. Thirdly, it ex- plores the content of Schafer's anti rational thought and its con- crete presentation in his works. This paper analyzes Schaefer's belief rebelling against rational thought from three angles. Firstly, from the perspective of rational power rulers, this paper analyzes the control of rationalism on individual free nature. Secondly, rational obstruction, that is, from the perspective of the weak and the ruled, analyzes their spiritual struggle against the representa- tives of rational power. Finally, the rational identity of rational figures is deconstructed. This provides a new research perspective for the irrational existence of human beings. In a word, Schaefer's plays are of great significance to people's understanding of the expansion of instrumental rationality and listening to the call of faith.